Monetary Finance : Do Not Touch, or Handle with Care? - Agur, Itai.; Capelle, Damien; Dell'Ariccia, Giovanni; Sandri, Damiano (Washington, D.C. : International Monetary Fund, 2022)
This paper reviews the theoretical arguments in favor and against MF and presents an empirical assessment of the risks that it may pose for inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet